Governance Assistance to Reinforce Sharia Financial in Sharia-Based Learning Management System (LMS) Startups - Nasharuddin Mas; Hanif Rani Iswari; Siti Nur Ainun (TGO Journal of Community Development, 2024)
Sharia-based financial management has become a necessity for many startups, especially those serving Islamic schools, pesantren, and foundations, given the Islamic values that underpin their operations. This article discusses the implementation of Sharia governance in startups providing Learning Management System (LMS) platforms for Islamic schools, pesantren, and foundations. This mentoring initiative identified the main challenges faced by startups, in particular limited understanding of Sharia principles in financial systems, difficulties in Sharia business contracts as syirkah, mudharabah, etc, and financial recording. Through a community service approach, we provide practical solutions to address these challenges to support the sustainability of Sharia-based startup businesses.